Cultivation of Entrepreneurial Psychology and Innovation Ability by New Media Art Under the Reform of Publishing Industry - Zhang, Mingjie; Song, Fangbin (Frontiers in Psychology, 2021)
In order to optimize the resource allocation of the traditional publishing industry in the new media era, it is proposed to integrate the traditional publishing and digital publishing industries to solve the problem of unbalanced resource distribution under dual-track conditions. Professional talents with innovative entrepreneurial ability and psychology in colleges and universities are cultivated to promote the integration and reform process of the publishing industry under the background of new media art. First, the study analyzes the digital reform issues facing the development of the publishing industry in the new media era. Second, in view of the development situation of the publishing industry in the Yangtze River Delta, it is proposed to establish a development model of integrated publishing in the Yangtze River Delta through resource allocation. Then, under the new media art form, the teaching mode of creative and entrepreneurial talents training in art colleges and universities is optimized to cultivate students' innovative ability and entrepreneurial positive psychology. The research results show that the number of books printed in Shanghai in the Yangtze River Delta is 13,000 types per year, and the number is still rising; however, periodicals and newspapers are affected by the new media industry, and the number of publications is declining. The printing volume has dropped by 50% in 9 years; the questionnaire survey results show that 68% of the students are very interested in entrepreneurial activities, but 53% of the students have not carried out entrepreneurial activities at all, indicating that the students' entrepreneurial ability is insufficient. The results provide a reference for studying the reform direction of the publishing industry and cultivating entrepreneurial talents in the context of new media.